The importance of adequate nutrition for children with ASD: A literature review (Research, Society and Development, 2023)
ASD is a neurological disorder with difficulties in communication, social interaction and repetitive behaviors. Its prevalence is 0.6% to 1%, and autistic children face eating problems, resulting in nutritional deficiencies that affect their long-term health and development. A literature review methodology will be carried out to analyze relevant studies on food selectivity in children on the autism spectrum and the therapeutic methods available to improve the quality of life and nutritional health of these children. The research was conducted using search tools such as PUBMED, SciELO and EBSCO. A lack of dietary variation and resistance to new foods is common in children with ASD, and this can result in the choice of highly palatable, less nutritious foods. This study aims to analyze how food selectivity affects the nutrition and development of children with ASD. autism, seeking strategies to improve their quality of life and well-being. It is concluded that food selectivity, dysbiosis and allergies impact the health of children with ASD. Excluding gluten and casein, probiotic/vitamin/mineral supplementation, and nutritional monitoring are effective. An adapted diet, low sugar consumption and more research are essential to better understand nutritional strategies in the treatment of dysbiosis and the needs of children with ASD.